Active Surveillance: Strategy to Reach The Unreported TB Patient In Hospitals - Aminah, Nenden Siti; Djuwita, Ratna; Sahanggamu, Paulus Daniel; Soelistyo, Soelistyo; Nasution, Helmi Suryani (Syntax Literate, 2021)
Background and Aims: The National Tuberculosis Program (NTP) conducted active surveillance to find unreported TB patients in hospitals. CTB supports by conducted active surveillance in 6 provinces. This study was conducted to see an overview of the implementation of active surveillance of TB cases in hospitals among districts supported by CTB and non CTB supported, including the challenges of active surveillance implementation to provide recommendations for National TB program. Methods: This study is a qualitative research with a case study design. Data collected by document reviews, observations, discussions, and in-depth interviews with key informants. Results: Only about 23% of TB cases from HIS are reported into SITT. This is partly due to the procedure or the flow of tuberculosis (TB) data from the Hospital to the National TB Program, which is a manuallly input by entry the data into the SITT.There are about 70% of cases that are not reportedly due to lack of human resources in the hospital to do data entry. Findings also show that districts supported by CTB have a percentage of cases gap less (4%-43%) than non CTB supported district (43%-74%). The data shows the importance of partnership or involvement of other partners in TB control programs. Conclusion: Active surveillance shows the need to strengthen hospital internal network. Standardized guideline and treatment monitoring mechanism should be established to support active surveillance nationwide. The NTP needs also to collaborate with the Directorate General of Health Services to establish a linkage between HIS and National TB surveillance system.